Efek Beras Analog dengan Substutisi Glukomanan Porang terhadap Fungsi Hati Mencit Diabetes Hasil Induksi Aloksan: Effect of Porang Glucomannan-Substituted Analog Rice on Liver Function of Alloxan-Induced Diabetic Mice - Melda Nurmaisari; Subeki Subeki; Sri Hidayati; Suharyono AS; Zuhrotul Mujayyanah (Jurnal Teknologi dan Mutu Pangan, 2026)
Diabetes melitus is a metabolic disorder that causes liver dysfunction. The use of functional foods made from local ingredients continues to be developed to help manage this condition. The objective of this study was to determine the effects of rice analogs substituted with porang glucomannan (Amorphophallus oncophyllus) and waxy cassava flour on liver function and body weight changes in diabetic mice induced by alloxan. The method used was a completely randomized design (CRD) with 6 replicates. A total of 24 male mice were divided into several groups: the healthy control group (AIN-93M diet), the diabetic group (AIN-93M diet), the diabetic group (porang analog rice), and the diabetic group (IR-64 rice). The results showed that feeding porang-analog rice resulted in a serum glutamate oxaloacetate (SGOT) level of 306±35.89 U/L, a weight loss of 0.92 g, and a Serum Glutamate Pyruvate Transaminase (SGPT) level of 180±14.96 U/L. In conclusion, consumption of porang glucomannan-based analog rice has the potential to maintain liver function while improving metabolic conditions in diabetic mice. It is hoped that this study can provide a scientific basis for the development of functional foods based on local ingredients to support liver health in cases of diabetes melitus.